Entry of antivirally active T lymphocytes into the thymus of virus-infected mice - Gossmann, J; Löhler, J; Lehmann-Grube, F (The Journal of immunology (1950), 1991)
The thymus has long been regarded as an immunologically "privileged site" by being shielded against the entry of exogenous Ag as well as protective elements of the immune system. After i.p. infection of mice, the lymphocytic choriomeningitis virus multiplied in this organ. Viral Ag was found predominantly in the epithelial-reticular cells of the medulla and to a lesser extent in such cells of the cortex. Beginning on day 7 after infection, the virus disappeared, a process that could be blocked by depleting the mice of peripheral T lymphocytes or of CD8+ cytotoxic T lymphocytes. Viral clearance was accelerated by i.v. injection of splenocytes from mice, which themselves were just eliminating the virus. CD8+ cells from CD8-congenic donor mice, most with blast morphology, were detected immunocytochemically in the thymus, predominantly in the medulla. A few CD8+ T lymphocytes from donors not previously infected were also demonstrated in the thymic tissue of infected mice. Our findings indicate that the lymphocytic choriomeningitis virus has access to the thymus and suggest that it is cleared by the antiviral activity of circulating cytotoxic T lymphocytes. Thus, just as other organs, the thymus appears to be subject to immune surveillance by mature T lymphocytes that have their origin in secondary lymphoid tissues.